2013
DOI: 10.1038/ncomms3006
|View full text |Cite
|
Sign up to set email alerts
|

Quantum nuclear dynamics in the photophysics of diamondoids

Abstract: The unusual electronic properties of diamondoids, the nanoscale relatives of diamond, make them attractive for applications ranging from drug delivery to field emission displays. Identifying the fundamental origin of these properties has proven highly challenging, with even the most advanced quantum many-body calculations unable to reproduce measurements of a quantity as ubiquitous as the optical gap. Here, by combining first-principles calculations and Importance Sampling Monte Carlo methods, we show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
128
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 50 publications
13
128
0
1
Order By: Relevance
“…25,29,45 In a previous study, we have already shown that based on the calculation of vibrationally resolved FranckCondon spectra in the frame of the TDDFT method, which includes the structural displacements upon changing the electronic state, the experimental emission spectrum of adamantane can be accurately reproduced. 28 Here, we have further exploited this approach and have obtained a very good agreement of the calculated vibrationally resolved spectra with their measured high-resolution counterparts for a large class of higher diamondoids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,29,45 In a previous study, we have already shown that based on the calculation of vibrationally resolved FranckCondon spectra in the frame of the TDDFT method, which includes the structural displacements upon changing the electronic state, the experimental emission spectrum of adamantane can be accurately reproduced. 28 Here, we have further exploited this approach and have obtained a very good agreement of the calculated vibrationally resolved spectra with their measured high-resolution counterparts for a large class of higher diamondoids.…”
Section: Resultsmentioning
confidence: 99%
“…Size-and shape-selected neutral diamondoids in the gas phase are optimal model systems for theory, especially for the study of quantum confinement effects. [20][21][22][23][24][25] In particular, doped or surface-modified diamondoids [2][3][4][5][6] as well as diamondoid dimers or trimers are extremely attractive as nanoscale building blocks for applications. Another interesting feature is the photoluminescence of diamondoids.…”
Section: Introductionmentioning
confidence: 99%
“…For the determination of band gaps in the solid state, both electron-phonon coupling and thermal expansion are important [24][25][26]. Studying the effects of electron-phonon coupling on the band gaps of solids from first principles has only recently become possible [22,[27][28][29][30]. In this paper, we combine the first-principles calculation of anharmonicity, electron-phonon coupling and thermal expansion to study the vibrational corrections to the thermal band gap of solid He and hence determine an accurate value for the metalization pressure including the effects of temperature.…”
mentioning
confidence: 99%
“…This expectation value can be calculated by writing the operatorÔ(Q) within a principal axes representation like that for the energy [22], or nonperturbatively by sampling phase space according to the nuclear density [28,30]. The first method is approximate, but the description is in terms of individual phonons, permitting direct access to the underlying physical processes.…”
mentioning
confidence: 99%
“…Recent years have witnessed a surge of interest in ab initio calculations of EPIs, leading to new techniques and many innovative applications in the case of metals and non-polar semiconductors [1][2][3][4][5][6][7][8][9][10][11][12]. In contrast to this fast-paced progress, in the case of polar semiconductors and insulators the study of EPIs from first principles has not gone very far, owing to the prohibitive computational costs of EPI calculations for polar materials.…”
mentioning
confidence: 99%